Keamanan Jaringan dengan Cowrie Honeypot dan Snort Inline-Mode sebagai Intrusion Prevention System - Tati Ernawati; Fikri Faiz Fadhlur Rachmat (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
Computer network systems have been designing to share resources. Sharing resources process, data security, and confidentiality are main issues in anticipating misuse of the access to information by unauthorized parties. The solution to anticipating these problems is the availability of a security system capable of handling various intruders who threaten the system and protect network resources. This study builds and analyzes the performance of computer network security using cowrie honeypot and snort inline-mode as an Intrusion Prevention System (IPS). The development process goes through the stages of analysis, design, implementation, and monitoring. The content analysis method has been using to explore the problems and requirements of the system built. The security system was build by configuring the IP address and network system devices (server, remote admin, client attacker). The test has been carrying out on 3 test parameters (confidentiality, availability, and integrity), comparison testing method has been using to test the integrity parameters. The test results indicate that the system functionality test for user needs have fulfilled, the results of the confidentiality test (83.3%), availability (93.3%), and the integrity of the inline-mode snort show faster response time (0.069 seconds on average) and more CPU resource usage efficient (0.04% average) than the cowrie honeypot. IPS snort inline-mode overall integrity parameter testing is more recommended for used network security systems than cowrie honeypots.